Avaliação do controle autonômico cardiovascular, do glicogênio muscular e de citocinas plasmáticas em ratos escolióticos - Chingui, Luciano Júlio (Universidade Federal de São Carlos, 2013)
The anatomical alterations of spine have been researched in experimental and clinical studies. The present study focused the analysis on the three aspects. The scoliosis and the alterations on the metabolic profile of the paravertebral and pectoral muscles (study I), the scoliosis and stretching influence in the plasma citocines concentration (study II) and the status of cardiac autonomic function front the scoliosis implantation (study III). The three studies were performed with male rats, which were divided into different experimental groups, with a total n of 68 animals. For the scoliosis induction were applied a non-invasive model composed by vests made of polyvinyl chloride (PVC). All data were expressed as mean ± epm. For the statistical analysis the Kolmogorov-Smirinov test was applied to investigate the normality of the data, whereas studies I and II were followed by the variance analysis ANOVA and Tukey post hoc (p<0,05), in the study III were used the Student-t test or the sum of rank in the Mann-Whitney test (p<0,05). In the first study were applied vests to the scoliotic group since the initial growth phase (post weaning) until the sixth week of growth, however in the studies II and III the vests application went up to the twelfth week. To the achievement of the first study the rats were divided into 2 experimental groups with n=6: control (C) and scoliotic (S). The outcomes from this study showed a reduction on the relation total protein/DNA, in the glycogen content and in the total weight of the scoliotic animals. This study established a homeostatic impairment of the pectoral and paravertebral muscles during the scoliosis induction process. In the second study the animals were distributed into 4 groups with n=8: control (C), stretched (S), scoliotic (SG) and stretched scoliotic (SS). The stretching consisted in 3 series of 30 seconds with 10 seconds of interval among the series. The results revealed an important increase in the concentration of IL-2, IL-6 and e TNF-α in the scoliotic group, whereas the intervention with stretching exercises could achieve a decrease of 4, 9 and 6% respectively on the concentration increase. These results suggest that the proposed model used to induce the scoliosis lead to a muscular disuse and the stretching has showed to be effective to minimize the deriving consequences of this disuse. In the third study the animals were divided into 2 groups again, control group (C, n=12) and scoliosis group (S, n=12). On this study the attention referred to possible alterations in the cardiovascular autonomic control system. Evaluations of heart rate variability, cardiac autonomic tonus and cardiac baroreflex sensitivity. From these results was possible to certify that scoliosis causes an alteration in the autonomic control, being that the scoliotic group presented best sympathetic modulation, greater vagal tone and greater cardiac baroreflex sensitivity. The outcomes suggest that scoliosis promote alterations in the autonomic function of the cardiac system. In general, the results from this study demonstrated that the scoliotic animals have smaller glycogen reserves and lower ratios of total protein/DNA; higher concentration of the citocines IL-2, IL-6 and TNF-α, while the scoliotic and stretched rats have lower concentrations from the same citocines; referring to the autonomic modulation the scoliosis led to a higher total variance, greater sympathetic cardiac modulation, greater vagal tono and best baroreflex sensitivity proving a better condition in the cardiovascular autonomic function through the most part of the evaluated items in the scoliotic rats.
Keywords: Fisioterapia; Escoliose; Exercícios de alongamento; Interleucinas; Frequência cardíaca; Pressão arterial; Análise espectral; Scoliosis; Skeletal muscle; Stretching exercises; Interleukin; Heart rate; Arterial pressure; Spectrum analysis; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL